Public awareness and attitudes toward epilepsy in different social segments in Brazil - ISABEL C. SANTOS; MARILISA M. GUERREIRO; ADRIANA MATA; RENATA GUIMARÃES; LEDA FERNANDES; DJALMA C. MOREIRA FILHO; CARLOS A.M. GUERREIRO (Arquivos de Neuro-Psiquiatria)
PURPOSE: To assess public awareness and attitudes toward epilepsy in Brazilians of different cultural and socioeconomic backgrounds. BACKGROUND: Several studies have examined public awareness and attitudes toward epilepsy in various countries but there are no equivalent data for Brazil or South America. MATERIAL AND METHODS: We have applied the survey proposed by Caveness and Gallup , with some modifications and adaptations to four groups (I-IV) of subjects: I- 105 individuals accompanying patients to the Ophthalmologic outpatient clinic of the Hospital das Clínicas of the State University of Campinas (UNICAMP); II- 93 students recently admitted to medical and nursing school; III- 101 senior non-medical students; and IV- 69 senior medical students. Groups II, III, and IV were students at UNICAMP. RESULTS: Individuals with a low socioeconomic standing had a poor profile of familiarity, knowledge and attitudes toward epilepsy. The pre-university and university students had a relatively good profile when compared to the published international polls. Senior medical students had an excellent level of familiarity and knowledge, but showed no change in their objection to having a son or a daughter marry an epileptic person. CONCLUSIONS: Our data suggest that there is a clear-cut relationship between the level of education and the individual's familiarity and attitudes toward epilepsy. Effective elimination of the prejudice toward epilepsy requires specific training and not just general, superficial information about the condition.